Gota d água de Chico Buarque e Paulo Pontes: o trágicomusical, criação e historicidade - Lourenço, Marise Gândara (2010)
The corpus used for this study was the tragic-musical piece Gota d água, written by Chico Buarque and Paulo Pontes in 1975. This literary work was conceived of in the most authentic Brazilian style; at the same time, romantic and revolutionary. It represents the rescue of leftist art, in the 1950s and 1960s. The authors of the referred musical piece, intentionally, elect the word as its dramatic center, valuing the word through verses and transforming it into a revealing historical moment in the 70 s. Additionally, they put the people as the central focus of their discourse as they considered it the only way to rescue the Brazilian cultural identity. Therefore, an analytical musical-theatrical study of the literary work Gota d água was carried out, under a literary and historical perspective, taking as a starting point Chico Buarque s and Paulo Pontes s ideas expressed in the preface of the piece and in an interview to Fernando Peixoto, entitled Subúrbio e Poesia (Suburb and Poetry). This piece is intended to be popular, but it adopts as a source text Medeia, an erudite piece, by Euripides (480- 405 a. C.). In order to elucidate this theater, we developed a comparative analysis, which revealed and enabled the understanding of the threads that compose this theater and the dynamics of these threads. Gota d água is a postmodern tragedy, which is actualized as historiographic metafiction with a realist text, although the staging is not, due to the fact that it incorporates the verse and the music. It is a popular theater, at the same time critical and national, whose tonic is the engagement, fulfilling itself as a radical art of protest and violence, an engaged musical theater.